21 Evaluation of Transdermal Flunixin Meglumine on Experimentally Induced Lameness in Adult Dairy Cattle. (10th April 2018) - Kleinhenz, M D; Gorden, P J; Smith, J; Schleining, J A; Kleinhenz, K E; Rea, D; Coetzee, J F
Abstract: Lameness is a common health issue with significant production and welfare implications. Flunixin meglumine is a nonsteroidal anti-inflammatory drug (NSAID) approved for use in cattle. Recently a new formulation of flunixin meglumine was approved which has transdermal absorption following topical application. Thirty (30) adult dairy cows at 60-90 days in milk, and in their 2nd or 3rd lactation, were enrolled in a study to determine the effect of transdermal flunixin on animals with induced lameness. Cows were allocated to one of three treatment groups. LAME + FLU : lameness induction + transdermal flunixin LAME + PLBO : lameness induction + placebo SHAM + PLBO : sham lameness induction + placebo Cows were dosed with transdermal flunixin at 3.33 mg/kg (1 ml/15 kg) every 24 hours for 3 doses or a placebo. The placebo was composed of propylene glycol and red-dye to mimic the test product. Lameness was induced by injecting 20 mg of amphotericin B into the distal interphalangeal joint of the left lateral digit. Outcome variables tested were plasma cortisol, substance P, visual lameness assessment, mechanical nociception threshold (MNT), and gait analysis using a pressure mat. Outcome measures were collected prior to lameness induction and at 8, 16, 24, 48, 72, 96, and 120 hours post-drug application. Cortisol levels for the LAME + FLU group were lower at all time-points compared to the LAME + PLBO and SHAM + PLBO groups (P = 0.0019). Substance P levels were not different among treatment groups (P = 0.92). Peak lameness scores were higher for the LAME + FLU group (2.7 ± 0.29) compared to the LAME + PLBO group (1.3 ± 0.42). At 72 hours, LAME + FLU cows returned to baseline lameness scores where LAME + PLBO cows were still lame. MNT levels between treatment groups were significantly lower for the LAME groups compared to the SHAM group (P = 0.0006). The MNT levels of the LAME + FLU cows increased over the study and returned towards baseline at 48 hours post-drug administration, indicating an increase for pain tolerance. For gait analysis, there were no differences between treatment groups when examining the affected left rear foot only. Force applied, contact pressure, step impulse, and stride length were similar. These results suggest multiple doses of transdermal flunixin meglumine may be needed to ameliorate lameness pain. Furthermore, the MNT results suggest the pain associated with lameness extends beyond when the animal becomes visually sound.